The Broken Dozen Mystery - Thomas, Jerry D.; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 1996)
Sammy and the other Shoebox Kids learn about helping others as they search for a missing painting from the Mill Valley Art Museum.
Keywords: Story Collection